Breastfeeding Self Efficacy dengan Pemberian ASI Ekslusif pada Ibu Menyusui di Desa Margorejo Kabupaten Pati: The Relationship of Breastfeeding Self Efficacy With Exclusive ASI Providing to Breastfeeding Mothers In Margorejo Village, Pati District - Moneca Diah Listiyaningsih; Wahyu Indah Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
Exclusive breastfeeding is very important for babies. In Central Java there is low breastfeeding coverage, namely in Pati Regency at 75.6%. The lowest breastfeeding coverage is at the Margorejo Community Health Center, namely 15.1% (Pati District Health Profile, 2022). In Margorejo Village, exclusive breastfeeding coverage is 3.39%. 9 out of 10 mothers who have babies aged 6 to 12 months in Margorejo Village do not breastfeed exclusively because the mothers feel unsure that they can breastfeed exclusively. Apart from that, other factors in the failure of exclusive breastfeeding include the mother's job, knowledge and social culture. To find out the relationship between Breastfeeding Self Efficacy and Exclusive Breastfeeding for Breastfeeding Mothers in Margorejo Village, Pati Regency The approach used uses a cross sectional approach. The population of this study consisted of 54 mothers with samples using total sampling. The data collection tool uses a questionnaire. Data normality test used the Shapiro-Wilk test, data analysis used the Chi-Square test. Of the 54 respondents of breastfeeding mothers, there were 30 respondents who had a high category of breastfeeding self-efficacy with exclusive breastfeeding, 16 respondents (53.3%) and 14 respondents (26.3%) in the non-exclusive breastfeeding category, while 24 respondents had low breastfeeding self-efficacy with exclusive breastfeeding. a total of 3 respondents (12.5%) and 21 respondents (84.5%) were not exclusively breastfed. The Chi-Square test shows the p value = 0.005 < α (0.05) that there is a relationship between breastfeeding self-efficacy and exclusive breastfeeding for breastfeeding mothers in Margorejo Village, Pati Regency.There is a relationship between breastfeeding self-efficacy and exclusive breastfeeding for breastfeeding mothers in Margorejo Village, Pati Regency ABSTRAK ASI eksklusif sangat pentingbagibayi. Di Jawa Tengah terdapat cakupan ASI yang rendah yaitu di Kabupaten Pati sebesar 75,6%. Cakupan ASI terendah terdapat di Puskesmas Margorejo yaitu sebesar 15,1% (Profil Kesehatan Kabupaten Pati, 2022). Di Desa Margorejo cakupan ASI eksklusifnya yaitu sebesar 3,39%. Sembilan dari sepuluh ibu yang memiliki bayi di usia 6 sampai 12 bulan di Desa Margorejotidak ASI eksklusif karena ibu merasa tidak yakin bahwa dapat memberikan ASI secara eksklusif. Selain itu, factor lain gagalya ASI eksklusif ada pekerjaan ibu, pengetahuan, dan social budaya. Untuk mengetahui bagaimana Hubungan Breastfeeding SelfEfficacy dengan Pemberian ASI Eksklusif pada Ibu Menyusui di Desa Margorejo Kabupaten Pati. Pendekatan yang dilakukan menggunakan pendekatan crosssectional. Populasi penelitian ini berjumlah 54 ibu dengan sampel yang menggunakan total sampling. Alat pengumpulan data menggunakankuesioner. Uji normalitas data menggunakan uji Shapiro-Wilk, analisis data menggunakan uji Chi-Square. Dari 54 responden ibu menyusui terdapat30 responden yang memiliki breastfeeding self efficacy kategori tinggi dengan ASI eksklusif sejumlah 16 responden (53.3%) dan 14 responden (26.3%) kategori tidak ASI eksklusif sedangkan dari 24 responden yang breastfeeding self efficacy rendah dengan pemberian ASI eksklusif sejumlah 3 responden (12.5%) dan 21 responden (84.5%) kategoritidak ASI eksklusif. Uji Chi-Square menunjukkan nilai p value = 0,005 < α (0,05) bahwa ada hubungan breastfeeding self efficacy dengan pemberian ASI eksklusif pada ibu menyusui di Desa Margorejo Kabupaten Pati. Ada hubungan antara breastfeeding self efficacy dengan pemberian ASI eksklusif pada ibu menyusui di Desa Margorejo Kabupaten Pati